Fostering Environmental Awareness Through Environmental Learning: A Cross-Country Study in Zambia, Brunei Darussalam, and Nigeria - Matilda Kanyampa Nakazwe; Masnah Mirasan; Angelica Effiong (Journal of Academic Biology and Biology Education, 2025)
Purpose of the study: This study examines the implementation of Environmental Learning in fostering environmental awareness and behavioral transformation among elementary school students across different developing-country contexts. The study addresses the limited comparative research on environmental learning practices and behavioral outcomes in diverse socio-cultural and educational settings. Methodology: A qualitative multi-site case study design was employed in three public elementary schools located in Lusaka (Zambia), Bandar Seri Begawan (Brunei Darussalam), and Calabar (Nigeria). Participants consisted of 90 students aged 9–11 years and six teachers selected through purposive sampling. Data were collected through classroom observations, semi-structured interviews, and document analysis. Trustworthiness was ensured through triangulation, member checking, expert validation (CVI = 0.91), and intercoder reliability procedures (Cohen’s Kappa = 0.86). Data were analyzed using thematic analysis and cross-case comparison. Main Findings: The findings indicate that Environmental Learning effectively promotes environmental awareness, environmental responsibility, and sustainable behavioral practices. Students demonstrated positive behavioral changes, including proper waste disposal, environmental cleanliness, resource conservation, and active participation in environmental activities. Cross-country analysis revealed contextual differences in implementation. In Zambia, environmental learning emphasized community participation and local environmental challenges; in Brunei Darussalam, implementation was supported by stronger institutional policies and sustainability-oriented school programs; while in Nigeria, community engagement played a central role despite infrastructure limitations. Novelty/Originality of this study: his study contributes to environmental education literature by providing comparative evidence from three developing countries and demonstrating how environmental learning promotes behavioral transformation through constructivist, experiential, socio-cultural, and environmental citizenship processes.